Distinct antibody profiles in HLA-B∗57+, HLA-B∗57− HIV controllers and chronic progressors. (15th March 2022) - Klingler, Jéromine; Paul, Nicodème; Laumond, Géraldine; Schmidt, Sylvie; Mayr, Luzia M.; Decoville, Thomas; Lambotte, Olivier; Autran, Brigitte; Bahram, Seiamak; Moog, Christiane
Abstract : Objective: Spontaneous control of HIV replication without treatment in HIV-1 controllers (HICs) was associated with the development of an efficient T-cell response. In addition, increasing data suggest that the humoral response participates in viral clearance. Design: In-depth characterization of Ab response in HICs may help to define new parameters associated with this control. Methods: We assessed the levels of total and HIV-specific IgA and IgG subtypes induction and their functional potencies – that is, neutralization, phagocytosis, antibody-dependent cellular cytotoxicity (ADCC), according to the individual's major histocompatibility complex class I (HLA)-B∗57 status, and compared it with nontreated chronic progressors. Results: We found that despite an undetectable viral load, HICs displayed HIV-specific IgG levels similar to those of chronic progressors. Interestingly, our compelling multifunctional analysis demonstrates that the functional Ab profile, by itself, allowed to discriminate HLA-B∗57 + HICs from HLA-B∗57 − HICs and chronic progressors. Conclusion: These results show that HICs display a particular HIV-specific antibody (Ab) profile that may participate in HIV control and emphasize the relevance of multifunctional Ab response analysis in future Ab-driven vaccine studies.